The Mine Haul Road Optimisation Alliance - An industry and academia collaboration - Handel, D.; Miedecke, J.; Thompson, Roger; Tomicek, E.; Tulloch, D. (2016)
The Mine Haul Road Optimization Alliance is an Australian industry-academia collaboration which has been developed to support mine haul road operators by fully integrating mine road design research solutions with industry end-user service providers to design, assess, implement and monitor the various equipment, materials and road management strategies required to optimize the safety, environmental and economic performance of a haul road. Initially, a broad overview of the university-industry collaborative landscape is presented, following which the current situation in the Australian mining sector is reviewed both nationally, and on a countrywide basis, internationally. This insight places realization of a collaboration between Curtin University Western Australian School of Mines Mining Engineering and Metallurgical Engineering (WASM ME2) and the Haul Road Optimization Alliance (HROA) industry members into context of opportunity. Following an overview of the HROA collaborative structure, aims and objectives, it is shown how academia and industry can collaborate to deliver a more robust solution to mine haul road design, performance or management needs, especially where integrated solutions are needed. Critically in this approach, implementation and monitoring data provided by industry and service-providers alike forms the foundation on which to develop research knowledge and innovation that is more responsive to the end-user requirements, typically represented by 'early goals' and implementable solutions. The paper concludes with examples of how the alliance collaborations work in practice to deliver improved mine haul road designs and optimized operational performance, together with the mechanisms used to ensure industry needs are met through focused, end-user driven research and integrated solutions implementation.